Injuries in professional women's elite soccer players in Kosovo: epidemiological injury study - Feim Gashi; Tine Kovačič; Ismet Shalaj; Bekim Haxhiu; Arben Boshnjaku (BMC, 2023)
Abstract Background An emphasis has been given lately towards women's engagement together with their potential in soccer. As this sport develops with athletes becoming more physically fit and skilled, it is unclear what the consequences in terms of injuries are. Having this in mind, this study aimed to investigate the major injuries that occur in women's soccer players. Methods This descriptive epidemiological study invited all 286 women's soccer players from the 12 participating women clubs in the Kosovo 1st Soccer League (elite football level) during the 2021/2022 season, out of which 142 from 12 clubs participated. Exposure time for 1000 h of playing and training were recorded in addition to the anthropometric data, playing position, and prior injury history during the end of the season, practice, and match. The exact type of injury, severity, and post-injury recovery time, as well as the circumstances surrounding the injuries, were recorded. Results In total 84 injuries were registered with an overall injury ratio (IR) being 3.21 (CI: 2.56, 3.98) injuries/1000 exposure hours. During the competitive season, each player sustained 1.4 injuries on average. IRs were significantly higher during competition (n = 50; IR = 1.57; CI: 1.52, 1.62) compared to training (n = 34; IR = 0.26, CI: 0.25, 0.27). Out of a total of 142 women players, 84 (59.2%) injuries occurred, and no record of injuries was made in 58 (40.8%) players. The overall IR was observed to be 3.21 (CI: 1.24, 3.27), with moderate and severe injuries accounting for 38.1% of total injuries (each), followed by mild (16.7%) and minimal (7.1%) injuries. Conclusion The women IR in Kosovo women's soccer players is low while being circa 11% below the international average. Almost 2 out of every 4 injuries were categorized as traumatic, with the IRs being more than 5-fold larger during games than during training. Additionally, these findings emphasize the higher rate of injuries amongst younger athletes, suggesting caution to be taken by the coaches when planning for the match. The collected data may help coaches and trainers create more targeted women's soccer injury prevention programs.